Challenges of Georgian Agriculture Sustainable Growth On The Sample Of Kakheti Region - Lali Chagelishvil-Agladze; Koba Chagelishvili (Foundations and Trends in Modern Learning, 2023)
Regions are very important for the sustainable development of the economy sustainable development, their economic potential fully and effectively use. Georgia has a very rich regional potential, which Purposeful and rational use ensures the region environmental safety and promotion of sustainable development village. Farming is one of the important factors of sustainable development Ecological and social efficiency will be achieved with the development, rural and Approaching the city. In this regard, the paper analyzes the agriculture of the Kakheti region potential. Its current state and possibilities of development. Only regional resource for sustainable development of agriculture ability is not the point. Also important regions of agriculture Infrastructural arrangement of settlements and townships, road and transport, financial institutions, communication systems/technologies, development, modernization of the healthcare system, insurance institutions broad implementation, development of service sector and services in general. On the other hand, it is necessary to improve the real sector of the region's economy, a new one creation of jobs, review of salary system, innovative steps take a step at the end of the paper, a conclusion is given, where the author approaches the village to the city and divides the work to be done for the formation of a strong village into three stages: I stage – Infrastructural, II stage - Social Policy, III stage - Education